Impaired microbial N‐acyl homoserine lactone signalling increases plant resistance to aphids across variable abiotic and biotic environments. (31st July 2022) - Sanchez‐Mahecha, Oriana; Klink, Sophia; Heinen, Robin; Rothballer, Michael; Zytynska, Sharon
Abstract: Beneficial bacteria interact with plants using signalling molecules, such as N ‐acyl homoserine‐lactones (AHLs). Although there is evidence that these molecules affect plant responses to pathogens, few studies have examined their effect on plant‐insect and microbiome interactions, especially under variable soil conditions. We investigated the effect of the AHL‐producing rhizobacterium Acidovorax radicis and its AHL‐negative mutant (does not produce AHLs) on modulating barley ( Hordeum vulgare ) plant interactions with cereal aphids ( Sitobion avenae ) and earthworms ( Dendrobaena veneta ) across variable nutrient soils. Acidovorax radicis inoculation increased plant growth and suppressed aphids, with stronger effects by the AHL‐negative mutant. However, effects varied between barley cultivars and the presence of earthworms altered interaction outcomes. Bacteria‐induced plant defences differed between cultivars, and aphid exposure, with pathogenesis‐related and WRKY pathways partly explaining the ecological effects in the more resistant cultivars. Additionally, we observed few but specific indirect effects via the wider root microbiome where the AHL‐mutant strain influenced rare OTU abundances. We conclude that bacterial AHL‐signalling disruption affects plant‐microbial interactions by inducing different plant pathways, leading to increased insect resistance, also mediated by the surrounding biotic and abiotic environment. Understanding the mechanisms by which beneficial bacteria can reduce insect pests is a key research area for developing effective insect pest management strategies in sustainable agriculture.